Contextual Science Learning Based on Local Wisdom: An Effort to Improve Science Process Skills in Primary Schools - Rapsanjani, Hafsemi; Yohanes, Rizki Adri; Fredy, Fredy (Universitas Pendidikan Mandalika, 2025)
This study aims to examine the effect of contextual science learning based on local wisdom on improving the science process skills of primary school students. The local context used in this study is the cultural practice of the Malind community in processing sagu sep using the stone-burning technique, which correlates with the subject matter of heat transfer. The research was conducted at SD YPK Tanas, involving 20 fifth-grade students as participants. A pre-experimental approach with a one-group pre-test and post-test design was employed. The research instrument consisted of essay-based tests covering five indicators of science process skills: problem formulation, hypothesis development, variable identification, data analysis, and drawing conclusions. Data analysis revealed a significant improvement across all indicators, with an average N-Gain of 0.82, categorized as high. The highest increase was observed in data analysis (N-Gain 0.88), followed by variable identification (0.85) and problem formulation (0.81). These findings indicate that science learning integrated with local cultural practices can enhance students’ understanding of heat transfer concepts and foster meaningful mastery of science process skills. Contextual learning based on local wisdom not only reinforces scientific concepts but also bridges science with students’ real-life experiences.